2017
DOI: 10.1177/1084822316685517
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Physical Activity Levels in Filipino Americans With Hypertension Using the Rapid Assessment of Physical Activity Questionnaire

Abstract: Regular physical activity decreases the risk of cardiovascular disease and premature death. Little research has been conducted among Filipino Americans about their level of physical activity. Using the validated Rapid Assessment of Physical Activity questionnaire, we examined the activity level of Filipino Americans (N = 108) from the southwest region of the United States and compared the findings with national physical activity guidelines. The sample mean age was 65 years, 98% were born in the Philippines, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Filipinos with CMD tended to be more inactive. This tendency is consistent with previous studies reporting that Filipinos with hypertension participated less in physical activity per day than non-hypertensives ( Garcia et al, 2010b ; Lee & Kahende, 2007 ) and that their exercise levels failed to meet national guideline recommendations ( Angosta & Serafica, 2017 ). Studies have shown that physical activity levels among the general population of Filipinos tend to be lower than those of other Asian subgroups ( Ye et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…Filipinos with CMD tended to be more inactive. This tendency is consistent with previous studies reporting that Filipinos with hypertension participated less in physical activity per day than non-hypertensives ( Garcia et al, 2010b ; Lee & Kahende, 2007 ) and that their exercise levels failed to meet national guideline recommendations ( Angosta & Serafica, 2017 ). Studies have shown that physical activity levels among the general population of Filipinos tend to be lower than those of other Asian subgroups ( Ye et al, 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…PA has the potential to prevent and manage hypertension, illustrating the need to address PA interventions among those who have hypertension in order to further control their disease. Studies that have examined blood pressure control behaviors found that Filipinos and Koreans with hypertension or poor health management (e.g., lack of blood pressure screening) exhibited lower PA levels and less likeliness to meet PA guidelines, as well as only 20% of Korean women had awareness of PA as a lifestyle behavior for controlling hypertension [44,45,46]. In our study, Koreans and Filipinos who reported monitoring their blood pressure were more likely to belong to the moderately active PA category (48.03% and 46.98%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the well-known benefits of PA, there are significant disparities in participation rates among specific racial/ethnic minority populations [7]. Asian Americans have reported lower rates of PA in comparison to Non-Hispanic Whites and other ethnic groups [8,9,10,11,12]. Due to national-level data identifying Asians Americans as a homogenous group, this has conveyed false measures regarding their health and specifically the hidden disparities in physical activity and chronic disease rates [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Filipinos represent the second largest Asian immigrant population in the US, yet the behaviors affecting PA among this population are largely understudied [17]. Studies that assessed general PA levels among Filipinos in the northeast US found rates of participation to be lower than the national average [8,18]. In a recent study among Asian American subgroups in California, middle-aged (45-64 years) Filipinos had the lowest odds of meeting the American College of Sport Medicine's (ACSM) PA recommendations compared to other ethnic groups, including Chinese, South Asian, Japanese, Korean and Vietnamese [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation